The Strategic Role of ICT in Islamic Higher Education - Dody Yogaswara (Universitas Muhammadiyah Enrekang, 2023)
Times continue to change, cultural shifts continue to occur continuously. The world of education is no exception. It is inevitable that the erosion of information and communication technology will continue to touch the world of education. From management, learning and finances, the use of information and communication technology can be maximized.This research method is a qualitative research method with a case study approach. A case study is a model that focuses on